Draft genome sequence of a multidrug-resistant KPC-2 and SRT-2 co-producing Serratia marcescens strain isolated from a hospitalised patient in Chile. (June 2020) - Quezada-Aguiluz, Mario; Lincopan, Nilton; Cerdeira, Louise; Fuga, Bruna; Silva, Francisco; Barrera, Boris; Cifuentes, Marcela; Bello-Toledo, Helia; Opazo-Capurro, Andrés; González-Rocha, Gerardo
Abstract: Objectives: Serratia marcescens is a neglected opportunistic pathogen of public-health concern, especially due to its antimicrobial resistance features. Here we report the draft genome sequence of the first KPC-2 and SRT-2 co-producing S. marcescens strain (UCO-366) recovered from a catheter tip culture of a hospitalised patient in Santiago, Chile, in 2014. Methods: Whole genomic DNA of strain UCO-366 was extracted and was sequenced using an Illumina NextSeq platform. De novo genome assembly was performed using Unicycler v.0.4.0 and the genome was annotated by the NCBI Prokaryotic Genome Annotation Pipeline (PGAP) v.4.8. Genomic features were analysed using bioinformatic tools available at the Center for Genomic Epidemiology, the Comprehensive Antibiotic Resistance Database (CARD) and Pathosystems Resource Integration Center (PATRIC). Results: The genome size of strain UCO-366 was 5 267 357 bp, with a G+C content of 59.7% and comprising 5299 coding sequences (CDS), 42 tRNAs and 115 pseudogenes. The genome of UCO-366 also included an IncL/M plasmid. The resistome comprised various antimicrobial resistance genes (ARGs) conferring resistance to carbapenems, cephalosporins, aminoglycosides, sulfonamides, chloramphenicol, rifampicin and fluoroquinolones. Importantly, S. marcescens UCO-366 harboured bla KPC-2 and bla SRT-2, representing the first description of these β-lactamase genes in this species in Chile. Conclusion: Here we report the genome of the first KPC-positive multidrug-resistant S. marcescens strain identified in Chile, which co-harboured several ARGs. The genome sequence of S. marcescens UCO-366 provides an insight into the antimicrobial resistance characteristics of this species in this country and offers important data for further genomic studies on this critical priority pathogen.